Waste Culture and Isolation: Prisons, Toilets, and Gender Segregation. (12th September 2019) - Zurn, Perry
Abstract : After reviewing the use of isolation in US prisons and public restrooms to confine transgender people in solitary cells and single‐occupancy bathrooms, I propose an explanatory theory of eliminative space. I argue that prisons and toilets are eliminative spaces: that is, spaces of waste management that use layers of isolation to sanctify social or individual waste, at the outer and inner limits of society. As such, they function according to an eliminative logic. Eliminative logic, as I develop it, involves three distinct but interrelated mechanisms: 1) purification of the social center, through 2) iterative segregation, presuming and enforcing 3) the reduced relationality of marginal persons. By evaluating the historical development and contemporary function of prisons and restrooms, I demonstrate that both seek to protect the gender binary through waves of segregation by sex, race, disability, and gender identity. I further argue that both assume the thin relationality of, in this case, transgender people, who are conceived of as impervious to the effects of isolation and thus always already isolable. I conclude that, if we are to counter the violence of these isolation practices, we not only need to think holistically about eliminative spaces and logic, but also to richly reconceptualize relationality.